Risk Analysis of Delay in The Construction Project - Rio Kurniawan Budi Soeseno; Diah Ayu Restuti Wulandari; Koespiadi Koespiadi (NAROTAMA UNIVERSITY, Indonesia, 2021)
The complex problems that existed during the Field Implementation in the SMP Negeri 1 Surabaya project at that time caused some work that was not as planned both in terms of time, quality and cost which resulted in overbudget and overtime. When experiencing overbudget and overtime, it is necessary to have good cost, quality and time management. Good management should not only be owned by the project owner. The length of time to complete the project has a big effect on the increase in the overall project cost. Therefore, daily, weekly and monthly progress reports are needed to report work results and completion times for each project work item. Furthermore, this work is compared with the completion time of the plan so that the completion time can be controlled for each period. This is because the construction of the building has a delay in time so that it can cause disruption in some field operations. The analysis that I have done is viewed from all of them (owner and contractor). This study uses the AHP (Analytical Hierarchy Process) research method because AHP is used to derive the ratio scale of several paired comparisons that are discrete or continuous. Other problems such as inconsistencies in planners, supervisors, executors, and other authorities in the field, namely lack of communication and late making decisions such as changes in design and changes in calculations that are in implementation and planning so that the project results in time and cost delays, and other problems. such as material calculations and others, there are also delays caused by delays in making decisions in implementation. Because of that, the project for the Public Junior High School 1 in Surabaya experienced delays in several jobs, namely the foundation, column, ladder, and beam work, which should have been done in 1-2 months to 3-4 months. In terms of implementation, such as lack of communication between planners, supervisors and implementers as well as other authorized officials, a good communication is needed. So that it does not cause so many problems and can reduce delays in terms of implementation in the field.